Agricultural livelihoods, adaptation, and environmental migration in sub-Saharan drylands: a meta-analytical review. (1st August 2022) - Hoffmann, Roman; Wiederkehr, Charlotte; Dimitrova, Anna; Hermans, Kathleen
Abstract: Drylands in sub-Saharan Africa are strongly affected by the impacts of climate change. Temperature increases, changes in rainfall patterns, and land degradation pose serious threats to food security, health, and water availability in the region. The increase in livelihood insecurity can in turn trigger migration as a way to adapt or cope with stress. Based on 89 original case studies, this study uses review and meta-analytical techniques to systematically explore the relationship between environmental change, adaptation, and migration in rural areas in sub-Saharan drylands. We show that households use a diverse range of strategies to respond to environmental hardships in different livelihood and ecological contexts. While migration is common in some communities, it is of less relevance to others, and it can take various forms. Our findings indicate that migration is often used as a complementary strategy to other forms of adaptation, which can vary depending on situational needs. We use cluster analysis to identify adaptation clusters and show how linked response strategies differ by socioeconomic conditions. We find that migration can serve as a last resort measure for highly vulnerable groups, or be used in combination with in-situ strategies for diversifying income and adapting agricultural practices. Our results have important implications highlighting the role of local conditions and complementary forms of coping and adaptation for understanding environmental migration.